2019
DOI: 10.5847/wjem.j.1920-8642.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ventilation strategies during cardiopulmonary resuscitation

Abstract: BACKGROUND: Many controversies still exist regarding ventilator parameters during cardiopulmonary resuscitation (CPR). This study aimed to investigate the CPR ventilation strategies currently being used among physicians in Chinese tertiary hospitals. METHODS:A survey was conducted among the cardiac arrest team physicians of 500 tertiary hospitals in China in August, 2018. Surveyed data included physician and hospital information, and preferred ventilation strategy during CPR.RESULTS: A total of 438 (88%) hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…[33] Several evidences now indicate that biotrauma induced by mechanical ventilation not only affects the lung but also leads to further systemic infl ammation and organ dysfunction via the release of inflammatory cytokines. [7,26,[34][35][36] These factors, therefore, provide an explanation, at least in part, of why patients with a pulmonary source of infection have poorer outcomes.…”
Section: P=0001mentioning
confidence: 99%
“…[33] Several evidences now indicate that biotrauma induced by mechanical ventilation not only affects the lung but also leads to further systemic infl ammation and organ dysfunction via the release of inflammatory cytokines. [7,26,[34][35][36] These factors, therefore, provide an explanation, at least in part, of why patients with a pulmonary source of infection have poorer outcomes.…”
Section: P=0001mentioning
confidence: 99%
“…However, clinicians can wait when ECMO is working. [8] After full anticoagulation, the body's fibrinolysis mechanism dissolves the fi brin and the clot. In patients unresponsive to anticoagulation, ECMO can serve as a bridge to other defi nitive advanced therapies (for example, thrombolysis orthromboembolectomy) to reduce the thrombus burden.…”
Section: Discussionmentioning
confidence: 99%
“…Liu, et al reported that approximately 20% of the study participants preferred asynchronous continuous compressions before ETI during in-hospital CPR. 11 Nichol, et al reported that survival between OHCA patients who received continuous compressions and those who received interrupted compressions by EMS providers had no difference. 12 In the current literature, limited data on CPR performed with continuous compressions and asynchronous ventilation with BVM are available.…”
Section: Introductionmentioning
confidence: 99%